The Influence of Corporate Governance on the Relationship between Related Party Transactions and Audit Fees - Hamidreza Hajeb; Mohammad Banafi; Javad Nejatpour (International Journal of Management, Accounting and Economics, 2021)
The purpose of this study is to investigate the effect of corporate governance mechanisms on the relationship between related party transactions and audit fees. In this study, board size and duality role of CEO were selected as corporate governance mechanisms and their effect on the relationship between related party transactions and audit fees among 93 companies listed on the Tehran Stock Exchange in the 10-year period of 2011-2020 were investigated. For this purpose, three hypotheses were formulated to investigate this issue and research regression models were tested using the panel data method with the fixed effects approach. The results showed that there is a positive and significant relationship between related party transactions and audit fees. The results also indicate that corporate governance mechanisms (board size, CEO duality) have a negative and significant effect on the relationship between related party transactions and audit fees. In fact, the results indicate that auditors are increasing their audit efforts (reflecting audit fees) to address the risk associated with related party transactions. It also minimizes conflicts of interest, opportunistic behaviors of managers and, consequently, the risk associated with related party transactions by applying appropriate regulatory mechanisms.